Delayed perforation of the right ventricle by pacemaker/automated implantable cardioverter-defibrillator lead: A single-center experience - Sarvesh Kumar (Heart India, 2021)
Introduction: Cardiac perforation by pacemaker/automatic implantable cardioverter-defibrillator (AICD) lead can be a life-threatening emergency. Delayed cardiac perforation by pacemaker/AICD lead is defined as perforation occurring after a period of 1 month following pacemaker/AICD insertion. Delayed perforation is often difficult to identify at first and needs active intervention to prevent complications and death. Materials and Methods: Patients presenting with and operated upon for delayed cardiac perforation following pacemaker/AICD insertion were included in this study. The study was conducted between April 2019 and April 2020. Results: Three patients reported with delayed cardiac perforation after pacemaker insertion. All patients had syncopal episodes, and detection could be easily done using chest X-ray and trans-thoracic echocardiography (TTE). Two patients had active fixation leads used for anchoring the lead in the right ventricle (RV). Two patients were female, while one was a male, and all had perforation through the RV apex. Lead reposition was done in two cases, thereby preventing the need for placing additional leads, while a new lead was required in the third case. Conclusion: Early identification of cardiac perforation can be done easily with chest X-ray and TTE, but a high index of suspicion should be kept in mind. Surgical or fluoroscopic intervention may be planned depending on the available expertise and patient condition.